Implementasi Program Kampung Pintar di Desa Balak Kecamatan Songgon - Clarisa Adella; Dimas Imaniar; Leni Vitasari (Neolectura, 2023)
The purpose of this study is to ascertain how the Smart Kampung Program would be implemented in Balak Village, Songgon District (Study on the Regional Regulation No. 60 of 2017 concerning the Implementation of the Smart City Masterplan Through Banyuwangi Smart Kampung). The research method, which was qualitative descriptive analysis based on the Tachjan principle, was applied. The study's findings point up an implementor component, with the Balak Village Government focusing only on developing its human resources in order to ensure that its internal parties are knowledgeable about information and communication technology. This digital literacy training is prioritized for internal parties as part of the program execution to support the smart village program because internal parties must be able to stay up with the times where information and communication technology is constantly evolving. Details about the target: The community is the primary target of this smart village program, but the Balak Village Government has not implemented it to its full potential because internal parties were given priority with digital literacy programs so that internal parties could inform the public about public service information systems. Due to the lack of socialization of the smart village program addressing the public service information system in Balak Village, the Balak Village Government still struggles to communicate with the general public..